Certain aspects of eroticism in twentieth century western painting - Marais, Estelle (Rhodes University, Faculty of Humanities, Department of Fine Art, 1973)
In this essay eroticism will be examined as it appears in some twentieth century representational styles. The decision to concentrate on the representational styles is based on the fact that eroticism is by nature incompatible with the non-representational or non-objective movements in art. This incompatibility is rooted in the knowledge that eroticism is intrinsically and fundamentally a human experience and could therefore find expression only in an art which is concerned with human experience, i.e. experiences which refer to man, his nature and his relation to Nature. It would be oversimplified and grossly inaccurate to equate the nonrepresentational with the abstract, abstraction being an element present in all art to a greater or lesser degree. However, when abstraction has reached the stage where it can define its aims, as, in the words of Kandinsky, "widening the separation between the domain of art and the domain of Nature", (Lake & Maillard: A Dictionary of Modern Painting, p. 1) then it may also approach the realm of the non-representational. When Michel Seupher states, "I call abstract art all art that does not recall or evoke reality", (Lake & Maillard: A Dictionary of Modern Painting, p. 136) abstract and nonrepresentational art becomes fused into an inseparable unity. Erotic expression will then be incompatible with this degree of abstraction. Intro., p. 1.
Keywords: Erotic art; Painting, Modern -- 20th century